2022
DOI: 10.12932/ap-050719-0594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment response of chronic spontaneous urticaria according to age: A single-center Korean study

Abstract: Background: Little information exists regarding the incidence of chronic spontaneous urticaria (CSU) or differences in its characteristics according to age.Objective: To evaluate the incidence, clinical characteristics and treatment response of CSU according to age. Methods:The relevance of gender, age, history of allergic disease, pre-diagnosis duration, and treatment response were retrospectively evaluated in patients diagnosed with CSU at Pusan National University Hospital between 2011 and 2018.Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
3
1
0
Order By: Relevance
“…Data regarding the incidence ratio of CSU in pediatric patients are scarce; nevertheless, sex predilection data report an equal incidence between the two sexes [21]. We observed a female predilection (73.9%) in the pediatric group, which could be explained by their higher mean age of diagnosis (15 years), which was younger in other studies [12,22]. The mean age at diagnosis in the adult group was 45.7 years, consistent with the literature [19,20,22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Data regarding the incidence ratio of CSU in pediatric patients are scarce; nevertheless, sex predilection data report an equal incidence between the two sexes [21]. We observed a female predilection (73.9%) in the pediatric group, which could be explained by their higher mean age of diagnosis (15 years), which was younger in other studies [12,22]. The mean age at diagnosis in the adult group was 45.7 years, consistent with the literature [19,20,22].…”
Section: Discussionsupporting
confidence: 90%
“…Metabolic syndrome was the most common underlying condition in adults (35.9%). A similar prevalence rate was documented in a Republic of Korea study [22,23]. This outcome is higher than the prevalence reported worldwide (12.5-31.4%) and in Israel (10.6-20.2%) according to the definition considered [24,25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…19,[29][30][31][32][33][34] Only two studies reported the percentage of elderly among all CSU patients in the general population (15.6% and 31.5%), 34,35 while the percentage of elderly among CSU patients from single-center studies ranged from 6.7% to 21.7%. 20,[36][37][38][39][40][41][42] The percentage of elderly CIndU patients was reported in five studies. 32,34,[43][44][45] The highest proportion was described in a general population study (16.3%).…”
Section: Resultsmentioning
confidence: 99%